2011
DOI: 10.1029/2010ja016154
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous mesosphere-thermosphere-ionosphere parameter measurements over Gadanki (13.5°N, 79.2°E): First results

Abstract: [1] We report first simultaneous airglow, lidar, and total electron content measurements in the mesosphere-thermosphere-ionosphere system behavior from Gadanki (13.5°N, 79.2°E).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…At a low latitude region, the F layer dynamo is created by various factors such as traveling ionospheric disturbances (TIDs) (Mansilla, 2003). It is also relevant to note that apart from the above, vertical coupling arising because of upward propagation of mesospheric waves (Taori et al, 2011), internal gravity waves, TIDs (Makela et al, 2010) and GPS (Dashora et al, 2012) can also be the sources observed variability in ionospheric and atmospheric parameter disturbances (Leonovich et al, 2011). However, these aspects need further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…At a low latitude region, the F layer dynamo is created by various factors such as traveling ionospheric disturbances (TIDs) (Mansilla, 2003). It is also relevant to note that apart from the above, vertical coupling arising because of upward propagation of mesospheric waves (Taori et al, 2011), internal gravity waves, TIDs (Makela et al, 2010) and GPS (Dashora et al, 2012) can also be the sources observed variability in ionospheric and atmospheric parameter disturbances (Leonovich et al, 2011). However, these aspects need further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Long records of measurement of temperature from ground-based OH emissions (Bittner et al 2002;French and Mulligan 2010;French and Klekociuk 2011) are useful in determining long-term trends (see Sect. 7) There has also been effort to use two or more different types of ground-based instruments at the same site for additional insight into the dynamics (Ejiri et al 2009;Taori et al 2011).…”
Section: Measurements and Their Limitationsmentioning
confidence: 99%
“…Using the relative photon count measurements, the mesospheric OH and O 2 temperatures are estimated by the method described by Meriweather (1984). Details of MLTP and validation of results are discussed elsewhere (Taori et al, 2011(Taori et al, , 2012a.…”
Section: Introductionmentioning
confidence: 99%